PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA AKHLAK TERHADAP KINERJA BISNIS : STUDI KASUS PADA PT KPI RU V BALIKPAPAN - Abdul Hakim Mutafarrika; Heru Prasadja; Lamtiur H. Tampubolon (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the influence of leadership style and the implementation of Living Core Values (LCV) AKHLAK culture on business performance at PT KPI RU V Balikpapan. This research employed a quantitative approach with a sample of 100 respondents. The data analysis methods included validity testing, reliability testing, classical assumption testing, regression analysis, coefficient of determination analysis, path analysis, and hypothesis testing. The results of the study show that, partially, leadership style has a significant effect on business performance, with a t-value of 2.762 ( > t-table value of 1.985) and a p-value of 0.007 ( < 0.05). Likewise, the implementation of the LCV AKHLAK culture has a significant effect on business performance, with a t-value of 6.367 (> t-table value of 1.985) and a p-value of 0.000 ( < 0.05). Simultaneously, leadership style and the implementation of the LCV AKHLAK culture influence business performance, as indicated by an F-count value of 69.092 ( > F-table value of 3.09) and a p-value of 0.000 ( < 0.05). This is further supported by the coefficient of determination of 0.588, meaning that both variables explain 58.8% of the variance in business performance, while the remaining 41.2% is influenced by other factors not observed in this study. PT KPI RU V Balikpapan needs to integrate leadership development and the AKHLAK culture into its management strategies, as both factors significantly impact business performance. By strengthening these two aspects, it is expected that business performance can be further optimized.